How Children's Advocacy Centers law enforcement officers cope with work-related stress: impacts and approaches to self-care - Beer, Oliver W. J. (Policing and society, 2023)
Work-related stress has been identified as being harmful for law enforcement officers’ (LEOs) health. The absence of effective coping strategies exacerbates the negative psychophysiological impacts on health. The literature suggests that law enforcement employers and communities also feel the impact of stress among LEOs. This study addresses the gap in the current literature in terms of qualitative-based exploration of the personal and professional impacts of LEs working within Children's Advocacy Centers (CACs) and self-care and stress alleviation practices in response to environmental stressors. CAC LEOs’ responses to three open-ended responses were analyzed from a national survey in the United States. Thematic analysis was utilised to identify emerging themes in relation to the: (1) personal, (2) professional impacts of work-related stress, and (3) the self-care or stress alleviation strategies adopted by LEOs. LEOs face multiple personal and professional stressors that impact their coping behaviours and health outcomes. Variation exists among LEOs in terms of coping behaviours and requires further investigation. This study highlights several gaps in the literature, including the personal and professional impacts of work-related stress among LEOs and the subsequent coping strategies adopted by LEOs in response to stressful working environments. Future research should further explore the impacts of work-related stress, coping strategies, and the development of effective stress prevention reduction approaches for this population.